Transtorno mental comum e lazer entre estudantes da área da saúde do campus de Botucatu-UNESP: um estudo transversal - Vieira, Júlia Lelis [UNESP] (2015)
Observational studies have shown an association between the presence of mental disorders and the lack of leisure time experiences. This study aims to evaluate the occurrence of CMD and its association with leisure time and activities among health students from the campus of Botucatu, UNESP. Method: This was a cross-sectional, descriptive and analytical study that analyzed aspects related to leisure time and common mental disorders. The dependent variable was the presence of Common Mental Disorder, investigated by the Self-Reporting Questionnaire. The main exploratory variable was leisure time, investigated by means of an specific tool for assessment practices Rest in the university population. The confounding variables were sociodemographic characteristics, support network, assessed by Social Support Scale (EAS) and alcohol use assessed by Alcohol Use Disorders Identification Test (Audit). The sample was composed of graduates from Nursing School, Medicine, and Nutrition in the campus of Botucatu, UNESP. Initially a descriptive analysis was performed, followed by bivariate analysis, and finally a logistic regression. The level of statistical significance pattern of p <0.05, to reject the null hypothesis, was adopted. Results: The overall prevalence of CMD was of 40.9% being 57.5% among students from Nursing School, 40.7% in Medicine and 26.6% in Nutrition. After logistic regression, the variables that remained significant risk factors were: Nursing School followed by Medicine; not being single; having difficulty making friends; feeling rejected; being dissatisfied with the choice of the course; desire to leave the course; dissatisfaction with the frequency of leisure time; use of alcohol, tobacco and / or psychoactive substances at leisure time; lowest score in support interaction; not playing sports and not playing instruments or singing. Conclusion: It was observed that the prevalence of CMD was similar to that found in the studied ...